Frequency of nystagmus in retinitis pigmentosa patients - Hameed, Maryam; Mansha , Maryam; Shabir , Maham; Iftikhar , Maryam; Elahi, Usama; Zahid , Mawra (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the frequency of nystagmus experienced by patients with retinitis pigmentosa. Method: The descriptive study was conducted at the University of Lahore Teaching Hospital, Lahore, Pakistan, from May to August 2024, and comprised patients aged 5-50 years receiving care for retinitis pigmentosa. To assess the kind and degree of retinitis pigmentosa, the patients were subjected to anterior segment examination, cover-uncover test, and pen torch examination. Data was analysed using SPSS 20. Results: Of the 25 patients with a mean age of 27.16 ±11.28 years, 16 (64%) were females. Overall, 15 (60%) patients were classified as blind, and 5 (20%) retained normal visual acuity. Nystagmus was present in 8 (32%) of the participants, predominantly among those with blindness (p= 0.377). Nystagmus was more frequent in females (6/16; 37.5%) than males. However, the difference was not statistically significant (p=0.734). Conclusion: Bilateral blindness was the predominant outcome, with nystagmus affecting nearly one-third of patients regardless of visual acuity. Key Words: Nystagmus, Patient, Retinitis pigmentosa.